A Cationic Phosphapyramidane. Issue 49 (24th October 2016) - Lee, Vladimir Ya.; Sugasawa, Haruka; Gapurenko, Olga A.; Minyaev, Ruslan M.; Minkin, Vladimir I.; Gornitzka, Heinz; Sekiguchi, Akira
Abstract: Pyramidanes C[C4 R4 ] constitute a novel class of highly strained and reactive polyhedral clusters that attracted a great deal of attention of both theoreticians and experimentalists. Although well‐studied from the theoretical viewpoint, pyramidanes were synthetically inaccessible, and only very recently their very first isolable representatives have been described. In this Communication, we report on the synthesis and structural studies of the cationic pyramidane with the Group 15 element at the apex, namely, phosphapyramidane, an isoelectronic analogue of the neutral pyramidanes of the Group 14 elements. Abstract : Positive results : A cationic phosphapyramidane derivative is readily available by the straightforward procedure: by a reaction of the cyclobutadiene dianion dilithium salt [(Me3 Si)4 C4 ] 2− ⋅[Li + (thf)]2 with PCl3 (see figure). The peculiar structural characteristics, as well as the nature of the non‐classical bonding interaction between the P ‐apex and the C 4 ‐base, are discussed on the basis of both experimental and computational studies.